2010
DOI: 10.1007/s10532-010-9362-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of fenamiphos degrading bacteria

Abstract: The biological factors responsible for the microbial breakdown of the organophosphorus nematicide fenamiphos were investigated. Microorganisms responsible for the enhanced degradation of fenamiphos were isolated from soil that had a long application history of this nematicide. Bacteria proved to be the most important group of microbes responsible for the fenamiphos biodegradation process. Seventeen bacterial isolates utilized the pure active ingredient fenamiphos as a carbon source. Sixteen isolates rapidly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…The phylogenetic tree showed sister linage between sequences of xenobiotic degrading microorganisms. The same results were obtained by Cabrera et al (2010) who reported that fenamiphos degrading bacteria were more closely related than others, and suggested that nematicide degrading bacteria were grouped within a common microbial population which can be of great significance for the soil ecology.…”
Section: Discussionsupporting
confidence: 80%
“…The phylogenetic tree showed sister linage between sequences of xenobiotic degrading microorganisms. The same results were obtained by Cabrera et al (2010) who reported that fenamiphos degrading bacteria were more closely related than others, and suggested that nematicide degrading bacteria were grouped within a common microbial population which can be of great significance for the soil ecology.…”
Section: Discussionsupporting
confidence: 80%
“…Organophosphorus pesticides are degraded by many bacteria isolated from soil. For example, a Brevibacterium sp., Microbacterium esteraromaticum and other bacteria, were able to hydrolyse the P-O-C bond of fenamiphos (ethyl 4-methylthio-m-tolyl isopropylphosphoramidate) (Megharaj et al 2003;Caceres et al 2009;Cabrera et al 2010). Rhodococcus and Bacillus strains were also able to rapidly degrade methyl isothiocyanate (Warton et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…They were maintained under laboratory conditions in the dark at 14±1ºC. The targeted amount of fenamiphos applied in the field ranges from 10 to 45 mg/kg soil which results in the use of 6-10 kg/ha under practical conditions depending on the crop [16,17]. It was reported that normal field application rates of fenamiphos can vary between 0.5 and 10 kg/ha, equivalent to 5 and 100 mg/kg soil [18,19].…”
Section: Methodsmentioning
confidence: 99%